1982
DOI: 10.1002/tera.1420250310
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro teratogenicity of cyclophosphamide in rat embryos

Abstract: When Day 10 rat embryos were grown in culture containing cyclophosphamide, an hepatic microsomal fraction (S-9), and cofactors for monooxygenation, they developed characteristic malformations. When a fixed volume of CP was added to cultures the number of malformed embryos was increased and their growth decreased dependent upon the S-9 concentration. In one group of experiments S-9 was prepared from animals which had been pretreated with either phenobarbital (PB) or 3-methylcholanthrene (MCA). All embryos cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(12 citation statements)
references
References 18 publications
4
8
0
Order By: Relevance
“…Kitchin et al [66] used a microsome preparation to activate CP and provided additional support for the concept that the activation process was dependent on cytochrome P-450 monooxygenases. The involvement of these monooxygenases was further characterized by the work of Greenaway et a1 [67], who demonstrated that teratogenic activation was enhanced when phenobarbital-but not 3-methylcholoanthrene-induced rat liver S-9 preparations were used. In addition they showed that this activation could be inhibited by either metyrapone or carbon monixide, two known inhibitors of cytochrome P-450 monooxygenases.…”
Section: Cp Teratogenesis In Vltro Role Of Cp Metabolitessupporting
confidence: 68%
“…Kitchin et al [66] used a microsome preparation to activate CP and provided additional support for the concept that the activation process was dependent on cytochrome P-450 monooxygenases. The involvement of these monooxygenases was further characterized by the work of Greenaway et a1 [67], who demonstrated that teratogenic activation was enhanced when phenobarbital-but not 3-methylcholoanthrene-induced rat liver S-9 preparations were used. In addition they showed that this activation could be inhibited by either metyrapone or carbon monixide, two known inhibitors of cytochrome P-450 monooxygenases.…”
Section: Cp Teratogenesis In Vltro Role Of Cp Metabolitessupporting
confidence: 68%
“…Another possibility is that I3C inhibits the bio‐activation pathways employing P450s, thus not allowing CP to be transformed into its teratogenic metabolites, phosphoramide mustard and acrolein. Such interference with CP activation has been demonstrated by the use of carbon monoxide and metyrapone by Greenaway et al (1982). That does not explain the apparent exacerbation of teratogenic effects seen in the I3C 24‐hr treatment group.…”
Section: Discussionmentioning
confidence: 92%
“…MNEs were induced by transplacental treatment with CP [Greenaway et al, 1982;Gilani and Chatzinoff, 1983;Porter and Singh, 1988;Harper et al, 1989;Zemlickis et al, 1993;Chorvatovicova and Ujhazy, 1995;Enns et al, 1999]. In a preliminary range-finding experiment to select an adequate dose of CP, groups of two pregnant rats were given daily oral doses of either the vehicle (water) or 5, 10, or 20 mg CP/kg on the 16th to 20th day of pregnancy.…”
Section: Selection Of Cp Dose For Mne Inductionmentioning
confidence: 99%
“…In the present study, CP, a potent inducer of micronuclei that requires hepatic activation [Oesch-Bartlomowicz et al, 1990], was administered to pregnant rats. Although CP was administered after organogenesis to limit its developmental toxicity, the teratogenic effects of CP have been established previously [Greenaway et al, 1982;Gilani and Chatzinoff, 1983;Brade et al, 1986;Porter and Singh, 1988;Zemlickis et al, 1993;Krishna et al, 1995;Hellman and Vokes, 1996;Enns et al, 1999]. Three concentrations of CP were used in order to find a dose of the compound that induced a reasonably strong increase in MN frequency (Table I).…”
Section: Selection Of Cp Dose For Mne Inductionmentioning
confidence: 99%